Problem Solving Ability of Class VIII Students Viewed from Cognitive Style in Attention Relevance Confidence Satisfaction Model Assisted by Problem Cards - Sapto, Argiyanto Dwi; Suyitno, Hardi; Kartono, Kartono (Universitas Negeri Semarang, 2019)
This study aims to (1) find out the description of the quality of ARCS learning assisted by problem cards on mathematical problem solving abilities of students (2) obtain a profile description of students 'mathematical problem solving abilities with field dependent cognitive style (3) obtain a profile description of students' mathematical problem solving abilities with field independent cognitive style. This research is a mix method research with concurrent embedded design. The study population was VIII grade students of SMPN 22 Semarang. The research subjects were determined based on weak, moderate, strong field dependent categories and weak, moderate, strong field independent categories. Data collection techniques of this research were observations, tests, and interviews. The results of this study indicate that (1) ARCS learning assisted by problem cards is appropriate both quantitatively and qualitatively on students' problem solving ability (2) students with field dependent cognitive styles in solving mathematics problem are still globally and less detailed in writing information according to the questions, write the answers incorrectly, do not check the correctness of the work and do not compile the steps of solving problems in different ways (3) students with field independent cognitive style in solving mathematics problem are understand the problems more analytically and do not write the same thing contained in the question, simplify the problem using their own sentences, apply the planned problem solving steps and obtain the correct answer, check the correctness of the work but do not compose the problem solving steps in different ways.